2018
DOI: 10.5455/medarh.2018.72.145-147
|View full text |Cite
|
Sign up to set email alerts
|

Duplex System with Ectopic Ureter Opens into the Posterior Urethra: Case Report

Abstract: IntroductionDuplicated ureter or Duplex Collecting System is a congenital condition in which the ureteric bud, the embryological origin of the ureter, arises twice, resulting in two ureters draining a single kidney. This congenital anomaly is rare, and even rarer when the duplex system with ectopic ureter is present. This type of congenital anomaly is even more rarely diagnosed and surgically treated in adulthood.Case reportThis case report presents a case of a 32-year-old male, who had a duplex collecting sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
6
Order By: Relevance
“… Most duplicated systems are asymptomatic and diagnosed incidentally. However, where symptoms do occur (infection, reflux or obstruction), the patient is likely to have completely duplicated ureters [4] .  As such duplex kidney usually does not require any treatment, however, if complications occur intervention may be required.…”
Section: Resultsmentioning
confidence: 99%
“… Most duplicated systems are asymptomatic and diagnosed incidentally. However, where symptoms do occur (infection, reflux or obstruction), the patient is likely to have completely duplicated ureters [4] .  As such duplex kidney usually does not require any treatment, however, if complications occur intervention may be required.…”
Section: Resultsmentioning
confidence: 99%
“…La DU incompleta no suele ocasionar síntomas, ni daño renal alguno y su diagnóstico con frecuencia es incidental. (2) La Ley de Weigert-Meyer explica la DU completa. Plantea que el uréter que surge del polo inferior del riñón se inserta más cefálico y lateral en la vejiga y presenta un curso intramural corto que predispone al reflujo ureteral y el uréter que surge de la porción del polo superior, se inserta más caudal y medial, con frecuencia desarrolla un ureterocele y se asocia a obstrucción.…”
Section: Discussionunclassified
“…Es frecuente en el sexo femenino con una proporción 6:1, con respecto al masculino. (1)(2)(3) A su vez, la inserción ureteral ectópica (IUE) es una entidad rara cuya incidencia se estima del 0.05 al 0.025%. Con frecuencia se presenta con duplicidad ureteral (DU).…”
Section: Antecedentesunclassified
See 1 more Smart Citation
“…However, conservative treatment is not always possible. Milicevic et al, 5 reported the case of a patient with left ureteral duplication with ectopic lower ureter involvement in the posterior urethra, who underwent a superior polar nephrectomy since the upper renal was not functional.…”
Section: Discussionmentioning
confidence: 99%